Theology of Diversity: A Critical Analysis of Amin Abdullah's Thought - Isfawati Isfawati (LaKaspia, 2026)
This article examines the concept of the theology of diversity from the perspective of Amin Abdullah and its relevance to strengthening religious harmony in Indonesia. The study is motivated by the increasing socio-religious challenges within multicultural societies that are vulnerable to conflict due to exclusivism and absolute truth claims. Unlike previous studies that tend to be descriptive, this research emphasizes a critical analysis of Amin Abdullah’s integrative-interconnective paradigm as a theological approach capable of fostering inclusive and dialogical religiosity. This study employs a qualitative library research method using hermeneutical and critical analytical approaches toward Amin Abdullah’s works and related literature. The findings reveal that Amin Abdullah’s theology of diversity is constructed upon the integration of religious normativity and the historical realities of plural societies. Through the integrative-interconnective paradigm, Amin Abdullah proposes a model of religiosity that is open, tolerant, humanistic, and based on interreligious dialogue. This concept is highly relevant in strengthening religious moderation and implementing the trilogy of religious harmony in Indonesia. This study concludes that the theology of diversity not only contributes theoretically to the development of contemporary Islamic studies but also provides practical implications for building peaceful, inclusive, and harmonious social life within Indonesia’s pluralistic society